Epicardial fat in patients undergo laparoscopical-sleeve gastrectomy - Lolan, Faris M; Mahmood, Abdullah S; Al-Gburi, Yasser F (Vojenské zdravotnické listy, 2022)
Introduction: Obesity is increasingly reported to be a contributing factor to vascular diseases resulting in increased patient morbidity and mortality rates leading to increase healthcare expenses. More precisely, the lipid deposition in cardiac tissues is interesting, due to their direct contribution to the disease initiation, prognosis, and all subsequent patients' fate. We do focus on the determination of the link between changes in body mass index (BMI) and epicardial fat deposition concerning gastric operation.Objective: The objective of this work was to study the relationship between weight reduction and "epicardial thickness" after laparoscopic-sleeve gastrectomy.Methods: Critically-ill patients were recruited from private clinics and out-patients hospital clinics. Forty-two patients undergoing laparoscopic-sleeve gastrectomy due to morbid obesity were included in this research. Patients followed for four months after the operation.Results: The results of this work find there is significant weight reduction in these patients in parallel with a reduction of epicardial fat thickness.Conclusion: Patients who experience laparoscopic-sleeve gastrectomy showed a reduction in weight in a parallel reduction in epicardial fat thickness.
Keywords: Laparoscopy; Adipose Tissue; následné studie; Humans; morbidní obezita; laparoskopie; hmotnostní úbytek; Cardiovascular Diseases; tuková tkáň; Bariatric Surgery; Weight Loss; Gastrectomy; výsledek terapie; kardiovaskulární nemoci; Follow-Up Studies; lidé; perikard; gastrektomie; Treatment Outcome; bariatrická chirurgie; Pericardium; Obesity, Morbid